Sharia Banking Supervision in Indonesia: Legal Mechanisms and Implications - Nur Sania Dasopang (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This study examines the legal and institutional frameworks governing Sharia banking supervision in Indonesia, focusing on the roles and effectiveness of the Sharia Supervisory Board (DPS), the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and the coordination between the Financial Services Authority (OJK) and DSN-MUI. Employing a normative-juridical approach complemented by comparative analysis, the research integrates doctrinal review with empirical insights drawn from regulatory documents, interviews with practitioners, and analyses of financial literacy surveys. The findings reveal significant challenges, including limited independence and professional capacity of supervisory bodies, overlapping institutional mandates leading to regulatory ambiguity, and low public literacy and trust in Sharia-compliant financial products. The study contributes to the field by proposing an integrated Sharia governance model that combines doctrinal clarity with consumer literacy metrics, validated through comparative benchmarking with Malaysia's IFSA 2013 framework and practices in Gulf Cooperation Council (GCC) countries. Policy recommendations include enhancing the autonomy and accreditation of DPS, codifying DSN-MUI fatwas within OJK and Bank Indonesia regulations, and implementing nationwide Islamic financial literacy programmes. These measures aim to strengthen the transparency, accountability, and resilience of Indonesia's Sharia banking sector, thereby supporting its sustainable development and alignment with global best practices